What are cascading disasters?. Issue 1 (8th August 2019) - Alexander, David; Pescaroli, Gianluca
Abstract : Cascades have emerged as a new paradigm in disaster studies. The high level of dependency of modern populations on critical infrastructure and networks allows the impact of disasters to propagate through socio-economic systems. Where vulnerabilities overlap and interact, escalation points are created that can create secondary effects with greater impact than the primary event. This article explains how complexity can be categorised and analysed in order to find those weak points in society that enable cascading impacts to develop. Scenarios can be used to identify critical dependencies and guide measures designed to increase resilience. Experience suggests that many potential impacts of cascading disasters remain uninvestigated, which provides ample scope for escalation of impacts into complex forms of crisis.